Analisis Kelayakan Investasi Alat Hemodialisa : Studi Kasus RSUD Tarakan Provinsi Kalimantan Utara - Rudi Armansyah; Fitria Husnatarina; Milwan (Coopetition : Jurnal Ilmiah Manajemen, 2022)
The purpose of this study was to analyze the investment feasibility of hemodialysis equipment and the factors that influence the placement of hemodialysis equipment procurement in Tarakan Hospital, North Kalimantan Province. The informants of this research are Deputy Director General and Finance, General & Finance Division, general & equipment sub-section and employees who are considered capable of representing data of interest and will be used in this study. The research method used in this study is a qualitative method. The method used is Unit Cost to calculate the procurement of hemodialysis equipment by finding the procurement of hemodialysis equipment. Research Results 1) Investment Feasibility Analysis, namely: a) Based on the calculation of Net Present Value (NPV), the result is Rp. 10.112.890.205 (positive): NPV > 0. This means that the investment offer for the procurement of hemodialysis equipment according to the NPV is profitable. Procurement of hemodialysis equipment at Tarakan Hospital, North Kalimantan Province based on NPV calculations is acceptable/feasible to implement. b) Based on the calculation of the Payback Period (PP), a positive result is obtained, namely the Cumulative PV of Rp. This 7,597,778,675 shows that the closest time is 8 years. Based on the value of the Payback Period (PP), the investment in the procurement of hemodialysis equipment is feasible because the age of 8 years is less than the economics of hemodialysis equipment, which is 10 years. c) The results of the calculation of BEP from 2020 to 2030 for the value of services, the procurement of hemodialysis equipment is feasible. 2) Factors related to the anxiety level of hemodialysis Patients with internal causes and the age of adult patients tend to experience kidney failure. In this case it often occurs in men. Multiple adjustments to deal with multiple patient anxieties with multiple levels of medication. External factors from experience will also affect anxiety and support from the closest people, especially the level of knowledge that makes patients accept the treatment experience.